Freedom Of Navigation In The South China Sea: China’s Legal Positions And United States’ Freedom Of Navigation Operations - Eshanasir, Rifqy (Faculty of Law, Universitas Gadjah Mada, 2025)
Abstract This research questions how China’s legal positions regarding freedom of navigation (FON) differ from the United Nations (UN) Law of the Sea Convention (LOSC), and how these differences inform tensions in the South China Sea (SCS) vis-a-vis United States’ (US) Freedom of Navigation Operations (FONOPs). Such inquiry is important for tensions between the US and China as superpower states over international sea law risks undermining stability in the SCS. It finds the LOSC generally affirms FON across maritime zones with varying degrees of contestation from coastal state’s sovereignty or sovereign rights. Including in the SCS, FON is least restricted in high seas, faces contestation from coastal states’ sovereign rights in Exclusive Economic Zones (EEZs), and is most restricted by their sovereignty within territorial seas. Still, the LOSC limits coastal state authority through provisions guaranteeing foreign vessels’ innocent passage. Contrasting the LOSC, China adopts two key positions on FON: requiring prior authorization for warships’ passage through “territorial seas”, including in disputed islands, and opposing foreign surveillance within its EEZ. The legal bases and defences of these positions are critiqued and frequently challenged, including by US FONOPs entailing large naval vessels sailing near China’s maritime claims. These operations raise concerns about regional stability as they may be perceived as unilateral military assertions and risk straining US relations with allies, including Australia, with SCS-adjacent countries, and China. Abstrak Penelitian ini mengkaji bagaimana posisi hukum Cina terkait kebebasan navigasi (FON) berbeda dari Konvensi Hukum Laut (LOSC) Perserikatan Bangsa-Bangsa (UN) dan bagaimana perbedaan ini berkontribusi pada ketegangan di Laut Cina Selatan (SCS) dan Operasi Kebebasan Navigasi (FONOP) Amerika Serikat (AS). Penyelidikan ini penting karena ketegangan antara AS dan Cina sebagai negara adidaya atas hukum laut internasional berisiko merusak stabilitas di SCS. LOSC umumnya menegaskan FON di seluruh zona maritim dengan berbagai tingkat kontestasi dari kedaulatan atau hak berdaulat milik negara pantai. Termasuk di SCS, FON paling tidak dibatasi di laut lepas, menghadapi kontestasi dari hak berdaulat negara pantai di Zona Ekonomi Eksklusif (EEZ), dan paling dibatasi oleh kedaulatan mereka di laut teritorial. Namun, LOSC membatasi otoritas negara pantai melalui ketentuan yang menjamin lintas damai kapal asing. Berbeda dengan LOSC, Cina mengadopsi dua posisi kunci terkait FON, yaitu: mewajibkan izin dahulu bagi kapal perang untuk melintasi